Accumulation and partitioning of toxic trace metal(loid)s in phytoliths of wheat grown in a multi-element contaminated soil. (1st February 2022) - Liu, Linan; Song, Zhaoliang; Li, Qiang; Ellam, Rob M.; Tang, Jingchun; Wang, Yangyang; Sarkar, Binoy; Wang, Hailong
Abstract: Cropland contamination by toxic trace metal (loid)s (TTMs) has attracted increasing attention due to the serious consequential threat to crop quality and human health. Mitigation of plant TTM stress by silica amendment has been proposed recently. However, the relationship between the siliceous structure of phytoliths and TTMs in plants, and the environmental implications of phytolith-occluded trace metal (loid)s (PhytTMs) remain unclear. This study assessed the accumulation of five metal (loid)s, including lead (Pb), zinc (Zn), cadmium (Cd), copper (Cu) and arsenic (As), in the organic tissues and phytoliths of wheat grown in a mixed-TTM contaminated soil under both lightly and heavily contaminated conditions. The results show that the concentrations of plant TTMs and PhytTMs were significantly ( p  < 0.05) positively correlated, and higher in heavily contaminated wheats than those in lightly contaminated ones. The bio-enrichment factors between phytoliths and organic tissues were higher for As (1.83), Pb (0.27) and Zn (0.30) than for Cd (0.03) and Cu (0.14), implying that As, Pb and Zn were more readily co-precipitated with silicon (Si) in phytolith structures than Cd and Cu. Network analysis of the relationship between soil and plant elements with PhytTMs showed that severe contamination could impact the homeostasis of elements in plants by altering the translocation of TTMs between soils, plants, and phytoliths. The accumulation of TTMs in phytoliths was affected by the capacity of Si deposition in tissues and chelation of TTMs with silica, which could impact the role of PhytTMs in global biogeochemical TTM cycles. Graphical abstract: Image 1 Highlights: The concentrated silica develops into various phytolith morphologies in wheat plants. Phytolith encapsulates metal (loid)s through their co-precipitation process in plants. Heavily metal-contaminated soil leads to increased TTM accumulation in phytoliths. PhytTMs affect long-term TTM cycles of the cropland with multi-metal contamination.